AKTIVITAS ANTIOKSIDAN SERTA PENETAPAN KADAR b-KAROTEN, FLAVONOID DAN FENOL TOTAL EKSTRAK ETANOL LABU KUNING (Cucurbita moschata, (Duch.) Poir) - -, Nova Anggreni; Anggreni, Nova; Mulyaningsih, Sri; Saiful Bachri, Moch. (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Yellow pumpkin (Cucurbita moschata) is a horticultural plant belonging to the Cucurbitaceae family. Yellow pumpkin fruit contains polysaccharides, various vitamins (including β-carotene, vitamin A, vitamin B2, tocopherol, vitamin C, and vitamin E). The abundant β-carotene in yellow pumpkin fruit has been proven to have activity in combating the negative effects of free radicals. This study aimed to determine the levels of β-carotene, total flavonoids, total phenols, and antioxidant activity in yellow pumpkin fruit (Cucurbita moschata) extracted using the maceration method with 96% ethanol solvent. The extract was qualitatively tested using thin-layer chromatography (TLC) and quantitatively tested using a UV-Vis spectrophotometer. Antioxidant activity was performed using DPPH method. The total flavonoid content in the yellow pumpkin fruit extract was 1.8 ± 0.025 mgQE/g extract, and the total phenol content was 13.9 ± 0.04 mg GAE/gram extract. Meanwhile, the β-carotene content was 16.99%, and the antioxidant activity of the yellow pumpkin fruit extract resulted in an IC50 value of 12.13 ppm, which can be classified as a very strong antioxidant.